Communication crisis management of the public security policy: the social media landscape of the police in portugal - Andrade, José Gabriel (2022)
This chapter discusses crisis communication management in the Portuguese public security police digital landscape, mainly focused on social media. This is an exploratory investigation it is intended to understand how crisis communication management methodologies in the digital environment can be applied in police intervention, so its legitimacy is reinforced. The study is divided into two parts, the literature review, and the empirical research. The data was gathered together through an interview survey, with the participation of four public security police officers and four investigators. The inter- views were transcribed, and their content was analyzed. In an emergency situation, most of the actions are communication activities, so its management in the digital landscape—above all social media—is critical for the police success, as an institution under strong scrutiny and whose actions depend on the citizen cooperation. Communication is essential for building reputation and should be used in threats to legitimacy, and as a tool for reaching out to the community.